Avoiding the Learning Curve for Transcatheter Aortic Valve Replacement. (26th January 2017) - Gurevich, Sergey; John, Ranjit; Kelly, Rosemary F.; Raveendran, Ganesh; Helmer, Gregory; Yannopoulos, Demetris; Biring, Timinder; Oestreich, Brett; Garcia, Santiago
Abstract : Objectives. To evaluate whether collaboration between existing and new transcatheter aortic valve replacement (TAVR) programs could help reduce the number of cases needed to achieve optimal efficiency. Background. There is a well-documented learning curve for achieving procedural efficiency and safety in TAVR procedures. Methods. A multidisciplinary collaboration was established between the Minneapolis VA Medical Center (new program) and the University of Minnesota (established program since 2012, n = 219 ) 1 year prior to launching the new program. Results. 269 patients treated with TAVR (50 treated in the first year at the new program). Mean age was 76 (±18) years and STS score was 6.8 (±6). Access included transfemoral (n = 35, 70%), transapical (n = 8, 16%), transaortic (n = 2, 4%), and subclavian (n = 5, 10%) types. Procedural efficiency (procedural time158 ± 59 versus148 ± 62, p = 0.27 ), device success (96% versus 87%, p = 0.08 ), length of stay (5 ± 3 versus6 ± 7 days, p = 0.10 ), and safety (in hospital mortality 4% versus 6%, p = 0.75 ) were similar between programs. We found no difference in outcome measures between the first and last 25 patients treated during the first year of the new program. Conclusions. Establishing a partnership with an established program can help mitigate the learning curve associated with these complex procedures.